2013
DOI: 10.1371/journal.pone.0064031
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Bullying Prevention: Intervention in Taiwan

Abstract: BackgroundThis study aimed to explore the effectiveness of the cyber bullying prevention WebQuest course implementation.Methodology/FindingsThe study adopted the quasi-experimental design with two classes made up of a total of 61 junior high school students of seventh grade. The study subjects comprised of 30 students from the experimental group and 31 students from the control group. The experimental group received eight sessions (total 360 minutes) of the teaching intervention for four consecutive weeks, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 14 publications
1
20
0
3
Order By: Relevance
“…(), Schultze‐Krumbholz et al. () n ; Lee, Zi‐Pei, Scanstro, and Dalal () o ; Barkoukis, Lazuras, Ourda, and Tsorbatzoudis () p ; Roberto, Eden, Savage, Ramos‐Salazar, and Deiss () q .…”
Section: Resultsmentioning
confidence: 99%
“…(), Schultze‐Krumbholz et al. () n ; Lee, Zi‐Pei, Scanstro, and Dalal () o ; Barkoukis, Lazuras, Ourda, and Tsorbatzoudis () p ; Roberto, Eden, Savage, Ramos‐Salazar, and Deiss () q .…”
Section: Resultsmentioning
confidence: 99%
“…Reports have shown that youth (e.g., De Nies, Donaldson, & Netter, ; Michels, ; Smith‐Spark & Vandoorne, ) and a college student (Friedman, ) committed suicide after being cyberbullied. Despite growing media attention to the issue of cyberbullying, few cyberbullying prevention/intervention programs have been developed and evaluated (e.g., Lee, Zi‐Pei, Svanström, & Dalal, ; Menesini, Nocentini, & Palladino, ; Williford et al, ; Wölfer et al, ). Furthermore, these prevention programs have been developed for youth.…”
Section: Introductionmentioning
confidence: 99%
“…Las primeras evaluaciones de otros programas para la atención de cyberbullying (Chibnall, Wallace, Leitch y Lunhofer, 2006;Doane, 2011;Doane et al, 2016;Lee et al, 2013) impactaron solo en algunos de los indicadores que consideraron. Se retomó el caso del Brief Internet Cyberbullying Prevention Program, que ha realizado dos evaluaciones sobre su efi cacia, la primera de ellas (Doane, 2011) detectó un aumento de conocimiento del fenómeno y disminución de perpetración y actitudes favorecedoras de cyberbullying, pero no evidenció mejora en la empatía hacia las víctimas; posteriormente se revisó y probó el programa (Doane et al, 2016) y se confi rmó la mejora en los tres indicadores que ya había detectado la primera evaluación, además de que se incrementó la empatía hacia las víctimas.…”
Section: Discussionunclassified
“…Tal es el caso de los programas como Let's Fight It Together: What We All Can Do to Prevent Cyberbullying (Childnet, 2007), que recurre a videos cortos; Cyber Bullying: A Prevention Curriculum (Kowalski y Agatston, 2008), que consta de ocho sesiones; Brief Internet Cyberbullying Prevention Program (Doane, 2011;Doane et al, 2016), un programa breve en formato de video y las Webquest (Lee et al, 2013) desarrolladas en ocho sesiones de 45 minutos cada una.…”
Section: Discussionunclassified
See 1 more Smart Citation